W poszukiwaniu najstarszej literackiej wersji "cudu nad morzem" (Wj 13,17-15,21) - Lemański, Janusz (The Biblical Annals, 2016)
The article is dedicated to an analysis and assessment of the newest critical literary research works on Ex 13,17-15,21. The aim is to find the oldest literary version of the event. In the author’s opinion, it is to be searched in Ex 13,20-22; 14,5-7.10bA.11-14,19-20.21aA.24-25.27*.30-31* and attributed to the non-P authors, who place the entire event ‘by the sea’. In this version of events the Israeli people, after crossing the Egyptian border, found themselves in a desert. For the first time they have expressed some fears of their lives, which is known as ‘the motive of complaining’. They show fear of the pharaoh’s army, so Moses urges them not to fear because they would not see the Egyptians more and YHWH would fight for them. The description has a characteristic of a military battle, although the only acting against the Egyptian military power is the God of Israel. Thanks to a strong wind, which blew for the whole night, he dried the sea and the Israelites reached the other bank walking on dry land, when the Egyptians die when trying to escape pointing to the returning sea waters. The events have their own time scheme: night and danger, dawn and salvation. A final effect is showing by the Israelites a fear of YHWH and his servant Moses. In the author’s opinion this version has originated short time before the fall of Babylon and was written according to a motive of ‘the Day of YHWH’ in its version, which was in force in the utterances of prophets of the period of exile and later (the day of judgment of nations, as a beginning of the salvation of Israel).